Implementasi E-Government di UPT Balai Pengujian dan Sertifikasi Mutu Barang Dinas Perdagangan Provinsi Sulawesi Selatan - Rastiana, Rastiana; Hasran, Hasran; Gani, Tahir (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2024)
This paper aims to analyze how implementation of e-Government policy in the Implementing Unit Technical Hall Testing And Certification Quality Goods, Service Trading South Sulawesi Province. Study This was carried out in the Implementation Unit Technical because Makassar, as the Mother city of South Sulawesi Province, has applied public-based electronic. Study This nature is descriptive. The population covers Implementation Unit apparatus Technical Hall Testing And Certification Quality Goods, services/agencies government area, as well member public. Sample taken with purposive sampling method. For collecting primary data and secondary, I used method observation, interviews, questionnaires, and documentation. Collected data was analyzed using technique analysis descriptive quantitative data supported by qualitative data. Results study show that the system service-based computer in the Implementation Unit Technical Hall Testing And Certification Quality Goods Service Trading South Sulawesi Province is functioning well based on some indicators used​ in the study.